Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s1751731119001903
|View full text |Cite
|
Sign up to set email alerts
|

Review: Water medication of growing pigs: sources of between-animal variability in systemic exposure to antimicrobials

Abstract: On many Australian commercial pig farms, groups of growing pigs are mass-medicated through their drinking water with selected antimicrobials for short periods to manage herd health. However, delivery of medication in drinking water cannot be assumed to deliver an equal dose to all animals in a group. There is substantial between-animal variability in systemic exposure to an antimicrobial (i.e. the antimicrobial concentration in plasma), resulting in under-dosing or over-dosing of many pigs. Three sources of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…The measurements of water consumption did not reveal any decrease in consumption in the pens at the start of treatment suggesting that the taste of the drug was accepted by the animals. Individual water consumption by pigs is reported to be influenced by numerous factors including stress, boredom, environmental temperature, disease, feed type and constituents and water flow rates [ 18 ], but in our study, despite the same age, weight, environment, food and health status, the individual consumption varied considerably between the lambs. Soraci et al [ 6 ] showed that consumption in healthy animals was also dependent on social rank, even if the effect was lower for water than for feed consumption.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The measurements of water consumption did not reveal any decrease in consumption in the pens at the start of treatment suggesting that the taste of the drug was accepted by the animals. Individual water consumption by pigs is reported to be influenced by numerous factors including stress, boredom, environmental temperature, disease, feed type and constituents and water flow rates [ 18 ], but in our study, despite the same age, weight, environment, food and health status, the individual consumption varied considerably between the lambs. Soraci et al [ 6 ] showed that consumption in healthy animals was also dependent on social rank, even if the effect was lower for water than for feed consumption.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, the low in vitro solubility of one of the drugs, even after addition of a diluent, excluded it from further experiments. A recent review on water medication reported that this problem of solubility in the stock solution could also occur for other antimicrobial drugs [ 18 ]. In our study, one product was soluble at high concentrations for 2 h at +4 °C in the laboratory and the solution seemed homogeneous in the metering pump with no deposit on the first treatment day but eventually a deposit appeared both in the pump and the drinking troughs as the days went by.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several managers described challenges in dissolving these products in dosing pump stock solution containers or header tanks. This was unsurprising, as these three antimicrobials have much lower solubilities in water than other commonly used antimicrobials [21]. Antimicrobials must be fully dissolved and remain in solution at close to the target concentration for the entire dosing period if the prescribed dose is to be ingested, absorbed, and distributed within each pig [22].…”
Section: Sub-optimal In-water Antibiotic Dosing Practices That May Hamentioning
confidence: 99%
“…It is critical to life and must be provided in sufficient quantity and quality to the pig, but clarity on what this means is elusive (Patience, 2013). Little et al (2019) tackle a related topic, namely the use of water as a vehicle by which medications can be provided to pigs at therapeutic levels. This is a topic of growing importance since there is a widespread desire to reduce the delivery of medication via the feed, and water seems to be a logical alternative.…”
mentioning
confidence: 99%